THE INFLUENCE OF NATIONAL MUSIC ON THE SPIRITUAL DEVELOPMENT OF YOUTH (International Congress on Economics, Management and Business Studies, 2026)
This article examines the influence of national musical art on the spiritual development of youth from theoretical and socio-pedagogical perspectives. The educational potential of national music and its role in shaping moral values, aesthetic taste, and worldview are analyzed. Special attention is given to the philosophical views of Abu Nasr Farabi and Alisher Navoi on the significance of music in human perfection. The pedagogical importance of traditional Shashmaqom heritage in youth education is highlighted.
Keywords: national music, spiritual development, youth education, maqom, aesthetic education, national values.